DsbA-L Ameliorates Renal Injury Through the AMPK/NLRP3 Inflammasome Signaling Pathway in Diabetic Nephropathy - Yang, Ming; Luo, Shilu; Jiang, Na; Wang, Xi; Han, Yachun; Zhao, Hao; Xiong, Xiaofen; Liu, Yan; Zhao, Chanyue; Zhu, Xuejing; Sun, Lin (Frontiers in Physiology, 2021)
NLRP3-mediated inflammation is closely related to the pathological progression of diabetic nephropathy (DN). DsbA-L, an antioxidant enzyme, plays a protective role in a variety of diseases by inhibiting ER stress and regulating metabolism. However, the relationship of DsbA-L with inflammation, especially the NLRP3 inflammasome, has not been examined. In this study, we note that activation of the NLRP3 inflammasome and exacerbated fibrosis were observed in the kidneys of diabetic DsbA-L-knockout mice and were accompanied by decreased phosphorylation of AMP-activated protein kinase (AMPK). Moreover, correlation analysis shows that the phosphorylation of AMPK was negatively correlated with NLRP3 expression and tubular damage. In addition, the decreased AMPK phosphorylation and NLRP3 activation induced by high glucose (HG) in HK-2 cells could be alleviated by the overexpression of DsbA-L. Interestingly, the protective effect of DsbA-L was eliminated after treatment with compound C, a well-known AMPK inhibitor. Our findings suggest that DsbA-L inhibits NLRP3 inflammasome activation by promoting the phosphorylation of AMPK.